Varying degrees of advanced heart blocks in association with acute inferior myocardial infarction - Naeem, Kashif Bin; Jarrahi, Abbas; Abdulrazzaq, Najiba (Indian Journal of Case Reports, 2018)
Acute inferior myocardial infarction (MI) is often associated with heart blocks as acute occlusion of the right coronary artery (RCA) compromises flow to sinoatrial nodal and atrioventricular nodal branches that arise from the proximal and distal parts of RCA, respectively. This phenomenon can happen in up to 20% of the cases, is usually transient and rarely requires pacemaker implantation. Still, when present, it raises alarms and poses significant monitoring and management challenges to the physicians. We report a similar case where the patient presented with inferior MI complicated by complete heart block. The patient went through varying degrees of advanced heart blocks before finally reverting to normal sinus rhythm. Subsequent coronary angiogram showed total thrombotic occlusion of proximal RCA. To the best of our knowledge, such a case has not been described before in literature where a complete array of heart blocks is reported in the context of acute MI. This case illustrates the importance of recognizing advanced heart blocks in acute MI. Although usually transient, these arrhythmias need careful monitoring during the initial days after MI.